KEPASTIAN HUKUM SERTIFIKASI DAN LABELISASI HALAL PRODUK PANGAN - KN Sofyan Hasan (Faculty of Law, Universitas Jenderal Soedirman, 2014)
Halal certificate is a written fatwa MUI that states halal food products in accordance with Islamic law, aims to provide legal assurance to consumers. However, the existing regulations are still per-ceived sectoral, partial, inconsistent and not systemic. Moreover, the most fundamental thing is the halal certification is not an obligation (mandatory) for businesses but it is voluntary. Consequently, halal certification and halal label do not have strong legal legitimacy which results in legal uncer-tainty of halal food products. In regard to this, the draft of Law on Halal Product Guarantee that is still stalled in the House should be soon stipulated and MUI should be given the authority to issue halal certification and perform it through the Fatwa Commission LPPOM. In addition, the govern-ment serves as a regulator as well as supervisor in the implementation of the provisions of the law which cause justice uncertainty.Key words: halal certificate, the Indonesian Ulama Council, food products